Empowering Cibuntu Village: Continuous Training and Assessment For Asean's Best Homestay Excellence - Amalia Mustika; Wijayanti Dewi Prabandari; Vienna Artina Sembiring; Freddy Triono (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Cibuntu Tourism Village, located in Cirebon, West Java, is a village rich in natural, cultural, and culinary potential, and it boasts homestays that have previously received ASEAN-level awards. The aim is to assess and provide ongoing training to improve the quality of homestays in Cibuntu Village, with the hope of reclaiming the title of the best homestay at the ASEAN level. The methods used include presentations, assessments through Q&A sessions, direct observations, and facility evaluations. A comprehensive assessment was conducted on ten homestays based on two aspects: local wisdom and service quality. The results revealed that three out of the ten homestays assessed met the high criteria and were deemed worthy of being re-nominated for the ASEAN competition. The assessment scores of these three homestays were nearly identical, indicating the very high quality of each homestay. These findings suggest that the homestays in Cibuntu Village have great potential to compete at the international level with only minor adjustments through training. This community service initiative is hoped to provide continuous training, improve homestay service quality, and strengthen Cibuntu Village’s position as a leading tourism destination in sustainable homestay management.